Usability and potential impact of a web-based literacy-oriented intervention for community-dwelling patients with complex care needs: a mixed methods case report. - Pluye, Pierre; Granikov, Vera; Paquet, Virginie; Frati, Francesca; Balli, Fabio; Dai, Jiamin; El Sherif, Reem; Hong, Quan Nha; Grad, Roland M. (Journal of the Medical Library Association, 2026)
Background: Community-dwelling patients with complex care needs (hereafter "patients") seek information to choose optimal care. However, patients with low ehealth literacy often have difficulty finding trustworthy, easy-to-understand information. Improving their ehealth literacy can lead to multiple positive health outcomes. This study aimed to describe patients' perceptions of the usability and potential impacts of a web-based, ehealth literacy--oriented intervention. Case Description: To support patients in finding, appraising, and using online health information (the three core principles of ehealth literacy) we developed the Online Health Information Aid (OHIA), which includes a website, an educational video, and a game. An evaluation was conducted with five patients who received the intervention. Preintervention (Day 1) and post-intervention (Day 30) data were collected. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using content analysis. Quantitative and qualitative results were compared in a joint display. Participants included three women and two men aged 46 to 71 years (mean age: 62) with two to 11 chronic health conditions (mean: 5) and two to 20 medications (mean: 10). Participants found the website usable (e.g., "good tool"). For the video, usability scores were high (67%-96%; mean: 79%) with positive comments (e.g., "good and helpful"). However, the game's usability was lower (40%-78%; mean: 60%), and comments were negative (e.g., "complex and not readable"). For three participants, ehealth literacy levels (n=2) and/or knowledge for appraising online health information (n=2) increased post-intervention. However, they did not perceive any impact of the intervention. Conclusion: These results suggest that the OHIA intervention, specifically the website and the video, is a promising approach to improving ehealth literacy among people with lower education, and a family income below or around the poverty line, including patients with complex care needs.